Ethical Leadership terhadap Employee Well-being: Peran mediasi Job satisfaction - Nadia May Nanda; Heru Kurnianto Tjahjono; Nuryakin Nuryakin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Purpose - This study aims to analyze the influence of Ethical Leadership and Employee Well-being mediated by Job satisfaction.Methodology - The sampling technique used purposive sampling, which obtained as many as 126 nurses at PKU Muhammadiyah Bantul Hospital, Yogyakarta. The research data were analyzed using Structural Equation Modeling (SEM) assisted by the IBM SPSS AMOS 24.0 software analysis tool.Findings - The results showed that Ethical Leadersh was related to Employee Well-being mediated by Job satisfaction. With the high level of Ethical Leadership in PKU Muhammadiyah Bantul Hospital nurses influenced by Employee Well-being. However, the high level of Ethical Leadership in nurses will be more influenced by the indirect effect of Employee Well-being through Job satisfaction than the direct influence of Employee Well-being.Originality/Novelty - This study offers new insights into the management literature by highlighting that combating negativity in the nurse's workplace not only preserves Employee Well-being, but also enables organizations to take full advantage of the positive processes that Ethical Leadership makes possible through Job satisfaction.Implications -Efforts made by employees and the company are by increasing the ability and support that can help employees to continue to hone their psychological capital in the hope that they will be able to achieve career success personally and organizationally